Anti-Herpes Simplex Virus Efficacy of Silk Cocoon, Silkworm Pupa and Non-Sericin Extracts - Kanyaluck Jantakee; Panchika Prangkio; Aussara Panya; Yingmanee Tragoolpua (MDPI AG, 2021)
Herpes simplex virus (HSV) infections are prevalent worldwide and are the cause of life- threatening diseases. Standard treatment with antiviral drugs, such as acyclovir, could prevent serious complications; however, resistance has been reported specifically among immunocompromised patients. Therefore, the development of an alternative approach is needed. The silk cocoon derived from silkworm, Bombyx mori, has been recognized for its broad-spectrum biological activity, including antiviral activity; however, its effects against HSV infection are unknown. In this study, we investigated the inhibitory effects of silk extracts derived from the cocoon shell, silk cocoon, silkworm pupa and non-sericin extract, on blocking HSV-1 and HSV-2 binding to host cells, resulting in the inhibition of the virus infection in Vero cells. Non-sericin extract demonstrated the greatest effectiveness on inhibiting HSV-1 and HSV-2 binding activity. Moreover, the virucidal effect to inactivate HSV-1 and HSV-2 was determined and revealed that non-sericin extract also exerted the highest potential activity. Using the treatment of non-sericin extract in HSV-2-infected HeLa cells could significantly lower the HSV-induced cell death and prevent inflammation via lowering the inflammatory cytokine gene expression. The non-sericin extract was analyzed for its bioactive compounds in which gallic acid, flavonoid and xanthophyll were identified, and might have partially contributed to its antiviral activity. The finding in our study suggested the potential of silk extract as an alternative therapeutic treatment for HSV infection.